Comparing the contributions of tourism and non-tourism exports to economic growth in Malaysia. Issue 12 (10th September 2017) - Tang, Chor Foon; Cheam, Chai Li; Ong, Soon Chuan
Abstract : An in-depth study using data from 1974 to 2013 is conducted to assess the role of exports in Malaysia's economic growth through the neoclassical growth model. Unlike previous studies, we segregate exports into four major components, namely tourism, electrical and electronic (E&E), palm oil and rubbers. By doing so, we are able to assess the relative contributions of tourism and non-tourism (i.e. E&E, palm oil and rubbers) exports to Malaysia's economic growth. To achieve the objective of this study, we perform the cointegration, Granger causality and the variance decomposition tests. Our findings suggest that only tourism, E&E and palm oil exports significantly influence economic growth in the long-run. Likewise, our Granger causality results also suggest that only tourism, E&E and palm oil exports Granger-cause economic growth. Thus, it supports the tourism-led growth, E&E export-led growth (ELG) and palm oil ELG hypotheses in Malaysia. With reference to the contributions to economic growth, the long-run estimation results and the results of generalized variance decomposition consistently suggest that tourism is relatively more important than the three non-tourism exports, especially in explaining the long-term economic growth of Malaysia.